Uso de corredores florestais e matriz de pasto por pequenos mamíferos em Mata Atlântica - Henrique Santiago Alberto Carlos (2006)
The Atlantic Forest has a high deforestation history and is reduced today to only 7% of its original forest cover. Mainly in these scenarios with high fragmentation levels, forest corridors are proposed and, in the present study, they were implemented in order to connect populations between Atlantic forest remnant fragments in the district of Casimiro de Abreu, Rio de Janeiro. The use of forest corridors and the adjacent pasture matrix by small mammals has been assessed through the capture mark and recapture of these animals in two sets of areas, each one containing two fragments, one corridor and a matrix area. Monthly trapping sessions were conducted from august 2004 to October 2005. The areas were significantly nested, that is, the richest sets of species contained all the species present in the poorer ones. The two sets of areas presented an expressive difference on their number of captured species (eleven and six). Apart from the exotic species, was observed a decrease pattern on the number of species, with higher richness on fragments, then corridors, then the matrix. In general, the capture success and the time of permanence of individuals in the outside areas (matrix and corridors) were very low compared to the fragments. The pasture matrix showed to be an extremely inhospitable area, and with the exception of one capture of Akodon cursor, no native species has been captured. Corridors summed six captured species, but when compared to fragments, animals captured in the corridors presented a very small permanence time, usually less than one trapping session (four days), with the exception of Nectomys squamipes in one of the corridors. Nevertheless, the capture of arboreal species like Micoureus demerarae and Caluromys philander in the corridors, despite the immature state of development of the corridor vegetation, showed the importance of corridors in a region extremely fragmented and with a matrix so hostile as the one studied here. The present study shows the great potential of this conservation enterprise in fragmented regions, and proposes some criterion and complementary initiatives for the implementation and maintenance of those corridors in order to improve their efficiency.